Mushroom : Wealth of India - Kumari, Babita; Kumari, Babita (Dehra Dun : Bishen Singh Mahendra Pal Singh, 2022)
The book is a pictorial guide as well as a reference book for the identification of the rich and diverse mushroom wealth of India present in the different habitats with varying attitudes almost throughout the country. It accounts for 260 species of mushrooms belonging to 118 genera under 57 families. Each species is represented with one or more large colour photographs, along with a detailed macroscopic and microscopic description of the species. This gives information on colour, spore colour, utilitarian aspect, habitat, and distribution along with common names for easy identification in the field. Ethnomycological notes are also provided. A Key to identifying the species, an updated glossary, microscopic illustrations of different types of Spores, Basidia, Cystidia, Hymenophoral trama, different shapes of Pileipellis, and electron scanned Microphotographs have been provided to make identification easy. The book includes more than 320 photographs to aid in the identification
Includes references and glossary.
Keywords: Mushrooms; Fungi; Mycology